Perancangan sistem informasi akuntansi penerimaan kas berbasis web pada koperasi unit desa sarwa mukti - Sutanto, Aldy Tia; Karyadi; Kusumadiarti, Rini Suwartika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Web-Based Receipt Accounting Information System in the Sarwa Mukti Village Unit Cooperative has not been computerized, while the processing must be done as carefully as possible due to the limited amount of cash it has. This design aims to be expected to make it easier to carry out the wheels of cooperative activities, in each business unit and increase the accuracy and security of the required information. This study uses qualitative research and the object of research is the cash receipts accounting system. The results showed that cash receipts at the Sarwa Mukti Village Unit Cooperative came from costumer loan interest, costumer installment payments, and cash sales of product, and all processes of recording and receiving cash were still manual and relied on transaction evidence, namely notes and invoices. Thus causing transaction data errors to accur frequently, therefore it is recommended that transaction must be computerized so that data security and transaction evidence are no easily lost and also need to be developed according to the needs and development of technology in order to continue to support the transaction activities carried out.